PENGARUH PERAN SUAMI DALAM MELAKUKAN PIJAT OKSITOSIN TERHADAP KELANCARAN ASI PADA IBU NIFAS - Zubaidah, Zubaidah; Sari, Lia Artika; Suryani, Suryani (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Factors that can hinder exclusive breastfeeding are less milk production (32%), deficiency (32%), nipple problems (28%), and breast milk retention (25%). This occurs due to a lack of stimulation of the hormones prolactin and oxytocin which play a role in the smooth production of breast milk. Factors causing mothers not wanting to breastfeed their babies are insufficient milk production. Lack of milk production is a major reason for a mother to stop breastfeeding early. This research is a quasi-experimental study with a one group pre test-post test design, which aims to determine the effect of the husband's role in performing oxytocin massage on the smoothness of breastfeeding in postpartum mothers in the Working Area of the Tanjung Inpatient Health Center, Muaro Jambi Regency. This research was conducted on 15 -25 July 2023. The population in this study were all postpartum mothers on days 1-3 in the Working Area of the Tanjung Inpatient Health Center, Muaro Jambi Regency, as many as 15 respondents. The sample in this study were postpartum mothers on days 1-3. Accidental sampling technique. Statistical test using the Wilcoxon test. Most of the milk production in postpartum mothers before oxytocin massage was not smooth as many as 10 respondents (66.7%), after oxytocin massage was smooth as many as 13 respondents (86.7%), There was an influence of the husband's role in doing oxytocin massage on smoothness Breast milk in postpartum mothers with ρ value = 0.005 (ρ <0.05). The husband's role in doing oxytocin massage can increase the smooth production of breast milk in postpartum mothers. It is expected that health workers, especially midwives at puskesmas, will conduct counseling about oxytocin massage in classes for pregnant women, especially third trimester pregnant women who will face childbirth and involve their husbands in the training.